PERAN GURU TERHADAP SISWA YANG MENGALAMI KESULITAN MEMBACA PERMULAAN DI SD NEGERI ABADIJAYA 3 DEPOK - Thania, Rasendriya Kirei; Maksum, Arifin; Nurhasanah, Nina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to investigate the early reading challenges faced by students at SD Negeri Abadijaya 3 Depok and the role of teachers in overcoming these problems. A qualitative descriptive method was used in this study, with the homeroom teacher of class 2C and six students of class 2C who experienced early reading difficulties as research subjects. Data analysis was carried out using the Miles and Huberman model of qualitative data analysis techniques, including three stages: data reduction, data presentation, and verification of conclusions. The results of the study showed variations in reading abilities and challenges faced by students, including difficulties in recognizing and pronouncing diphthongs, and difficulties in composing words and reading fluently. Teachers have made maximum efforts to fulfill their roles as educators, managers, facilitators, supervisors, administrators, innovators, dynamicators, leaders, and evaluators. However, improvements are still needed in using more effective learning methods, creating a conducive classroom environment, and implementing innovations in reading learning.